(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kanyakumari District, located at the southern tip of India, has been a significant site for India’s struggle for independence. While many freedom fighters from this region have been recognized, several unsung heroes have made substantial contributions that remain largely unacknowledged. This paper aims to shed light on these lesser-known figures, examining their roles and the impact of their activism during the colonial era.